Production and profiling bioflavor compound from fermentation OPEFB hydrolysate and CPO by Lactobacillus sp. - Firda Dimawarnita; Azzakiyya Salsabila Syifa Kusuma; Urip Perwitasari; Elok Zubaidah; Yora Faramitha; Pijar Religia; Ario Betha Juanssilfero (Menara Perkebunan, 2024)
Bioflavor is a type of natural flavor that is obtained from microbial metabolites during the process of fermentation. Most of the bacteria involved in food fermentation are lactic acid bacteria, including Lactobacillus sp. The optimal medium for Lactobacillus sp. growth is de Man Rogosa and Sharpe (MRS), but it is considered to be less economical. Therefore, alternative carbon and nitrogen sources are needed. This study aimed to determine the bioflavor produced in de Man Rogosa dan Sharpe Broth (MRSB) media that was substituted with Oil Palm Empty Fruit Bunch (OPEFB) hydrolysate and Crude Palm Oil (CPO) at concentrations of 5, 15, and 30%, respectively by using gas chromatography-mass spectrometry. The results showed that substituting MRSB with 15% CPO produced the best results for the growth of Lactobacillus sp. However, each medium produced different bioflavor compounds. In the control media (MRSB), the highest amount of bioflavor compound was 2,3-dihydro-3,5-dihydroxy-6-methyl -4H-Pyran-4-one (rose tea). In the OPEFB hydrolysate-substituted medium, it was benzene-acetaldehyde (sweet, bread, rose), in the CPO-substituted medium, it was furaneol (pineapple and strawberry) and pyrazine (nutty, roasted coffee).